Respuesta :

Answer:

[tex]\frac{1}{42}[/tex]

Step-by-step explanation:

Since [tex]\frac{\sqrt{0+9}-3 }{sin7n} = \frac{0}{0}[/tex]

We should apply the L'Hopital Rule to find the limit. (Use this when we see [tex]\frac{0}{0}[/tex].

Take the derivative of the numerator and the denominator individually.

[tex]\frac{d}{dn} (\sqrt{n+9}-3) =[/tex] [tex]\frac{1}{2\sqrt{n+9} }[/tex]

[tex]\frac{d}{dn}(sin7n)[/tex] [tex]= 7cos(7n)[/tex]

So the new equation is:

[tex]\frac{1}{14cos(7n)\sqrt{n+9}}[/tex]

Now we can plug in n = 0 into the new equation:

[tex]\frac{1}{14cos(7*0)\sqrt{0+9}}[/tex]

Since [tex]cos(7*0) = cos(0) = 1[/tex]

[tex]\frac{1}{14*1\sqrt{9}}[/tex]

[tex]\frac{1}{14*3} = \frac{1}{42}[/tex]

Therefore the answer is [tex]\frac{1}{42}[/tex].

ACCESS MORE